Lessons learned from Long-term Soil Fertility Management Experiments in Africa - Bationo, Andre (Springer Netherlands, 2012)
This book elucidates the importance of long-term experiments in revealing evidence of soil fertility decline in Africa. An evaluation of experiences from on-going long-term experiments is given in broad detail. The first chapter explains the paradigm shift in soil fertility management then provides justification for long-term experiments before illuminating experiences from long-term experiments in East, West and Southern Africa. The second, sixth, eighth and ninth chapters give an in-depth account of crop management practices and soil fertility interventions in long-term trials within specific agro-ecological zones in West Africa. The rest of the chapters (chapter three, four, five and seven) address crop management, tillage practices and, organic and inorganic fertilizer applications in the context of long-term experiments in specific agro-ecological zones in East Africa.